Efektifitas Kewenangan dan Tanggung Jawab Pegawai Pencatat Nikah KUA Kota Tanjungpinang - Elza Syarief; Utha Chuandra (Journal of Law and Policy Transformation, 2019)
Submission of a marriage wish application is required to attach the requirements of the marriage document. Marriage Registration Officer who is given the authority of marriage registration attribution checks and examines the requirements that have been fulfilled according to the laws and regulations for marriage registration. But the reality is that after marriage registration, there are many marriages that are known to violate normative provisions and religious principles. This study uses a sociological juridical research method. As a result, there are still many types of marital law violations to be held accountable for these violations. In the event that there are known elements of marital law violations, there are 3 (three) forms of responsibility for Marriage Registrar, namely: administrative, criminal and civil liability.